Phytochrome-mediated shade avoidance responses impact the structure and composition of the bacterial phyllosphere microbiome of Arabidopsis - James A. O’Rourke; Stacey A. Vincent; Isabel E. I. Williams; Eleanor L. Gascoyne; Paul F. Devlin (Environmental Microbiome)
Abstract The shade avoidance response triggers a dramatic promotion of elongation growth, accompanied by a significant reprogramming of metabolic pathways as plants seek to prevent overtopping and adapt to vegetative shade. Here we demonstrate that simulated vegetative shade results in significant changes in the structure and composition of the phyllosphere bacterial microbiome. Our study uncovered significant shifts in the diversity, occurrence, abundance and activity of bacteria within the phyllosphere microbiome. A comparison of responses in both wild-type plants and phytochrome mutants, which inherently exhibit a shade-avoidance phenotype, revealed both indirect responses to host plant physiology and direct responses to light among the microbiota. Hierarchical clustering of response patterns further suggested that over a third of the taxa constituting the core phyllosphere microbiome in our assay show some degree of response to vegetative shade. Bacteria that increased in abundance on plants with a shade-avoidance phenotype corresponded to genera associated with beneficial traits such as enhanced disease resistance and growth promotion. Our findings suggests that plants manipulate their phyllosphere microbiome under shade conditions as a strategy to optimise fitness when competing for light. We discuss the implications of our findings in terms of furthering our understanding of plant-microbe signalling in the shaping of the phyllosphere microbiome and the possibility of manipulating the phyllosphere microbiome for plant health in an agricultural setting at high planting densities.